2013
DOI: 10.1088/1674-1056/22/5/058101
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of microwave absorption of nanocomposite BaFe12O19/α-Fe microfibers

Abstract: Xin-Chun(杨新春) a) , Liu Rui-Jiang(刘瑞江) b) , Shen Xiang-Qian(沈湘黔) a) † , Song Fu-Zhan(宋福展) a) , Jing Mao-Xiang(景茂祥) a) , and Meng Xian-Feng(孟献丰) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…13). Experimentally, a number of studies concerning the control of the microwave properties in different types of hard/soft systems (i.e., thin films, nanocomposites and core/shell nanoparticles) can be found in the literature [45,91,123,124,129,270,271,294,[342][343][344][345][346][347][348][349][350][351][352][353][354][355]. Many studies show that µ' and µ'' depend on the ratio of hard/soft materials both for core/shell nanoparticles [129,342,345], nanocomposites [45,[347][348][349][350][351][352] and bilayers [354].…”
Section: A) B)mentioning
confidence: 99%
See 2 more Smart Citations
“…13). Experimentally, a number of studies concerning the control of the microwave properties in different types of hard/soft systems (i.e., thin films, nanocomposites and core/shell nanoparticles) can be found in the literature [45,91,123,124,129,270,271,294,[342][343][344][345][346][347][348][349][350][351][352][353][354][355]. Many studies show that µ' and µ'' depend on the ratio of hard/soft materials both for core/shell nanoparticles [129,342,345], nanocomposites [45,[347][348][349][350][351][352] and bilayers [354].…”
Section: A) B)mentioning
confidence: 99%
“…Studies on both hard-soft core/shell nanoparticles and nanocomposites have demonstrated that the main parameters of R L can be controlled by the hard/soft ratio [45,91,123,129,271,294,[342][343][344][345][346][347][348][349][350][351][352].…”
Section: A) B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have tried to coat the ferromagnetic particles with non-magnetic layers. [9,10] Although the non-magnetic layer can reduce the eddy current effect, the outer coating is non-ferromagnetic, which will not be helpful for attenuating the incoming EM wave via the mechanism of magnetic losses. Therefore, here we aim to develop a core-shell nanocomposite consisting of both ferromagnetic phases.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Yang et al reported on microwave absorption properties of the nanocomposite BaFe 12 O 19 /α-Fe microfibers. [10] Ren et al investigated the nanocomposites consisting of SiO 2 @Fe 3 O 4 nanorods, Fe 3 O 4 @Fe nanopariticles and graphene and their efficient microwave absorption performances. [11,12] However, these materials are usually designed as a single-layer structure and hard to simultaneously meet the requirements for low weight and strong absorption in a wide frequency range.…”
Section: Introductionmentioning
confidence: 99%